MATURATION AND SPAWNING OF THE ANCHOVY THRYSSA MYSTAX IN THE NORTHERN ARABIAN SEA - Hoda, S M Shamsul (Indian Journal of Fisheries, 2011)
Maturity studies carried out on Thryssa mystax (Bloch & Schneider), collected from commercial landings at Karachi Fish Harbour, from January to December, 1977, show that the female-male ratio is 1.26 : 1, and, as revealed byova- diameter polygons, S’pawnmg occurs twice a year. There are two peak spawning seasons, in January-March and June-July, as borne out by the close approximation of GSI and relative condition coefficient. The minimum size at sexual maturity was about 140 mm TL for both sexes. The relations between total length of fish and length and breadth of gonads, and between fish weight and gonad weight have been determined. The logarithmic relationships between fecundity and total length and body weight and ovary weight have also been eatablished